Managing Interpersonal Service Competencies in Hospitality: A Cross-Cultural Study of New Zealand and Vietnam - Warren Goodsir; Phan Minh Chau; Tran Thi Huyen Trang (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2026)
Purpose of the study: This study aims to compare how hospitality organizations in New Zealand and Vietnam manage employee interpersonal service competencies through formal and informal control mechanisms. The study also examines how cultural differences, labor market conditions, organizational values, and hospitality management systems influence employee interpersonal behavior and service quality. Methodology: This study employed a qualitative comparative case study approach involving four-star hotels in New Zealand and Vietnam. Data were collected through semi-structured interviews with hotel managers and supervisors from Human Resource, Front Office, and Food and Beverage departments. The study also utilized document analysis and field observations to strengthen data validity. Main Findings: The findings indicate that hotels in New Zealand rely more heavily on informal control systems, organizational culture, employee autonomy, and self-regulation to manage interpersonal service competencies. In contrast, Vietnamese hotels emphasize formal control systems, hierarchical supervision, standardized procedures, and direct managerial monitoring. New Zealand hotels prioritize authenticity, emotional intelligence, and guest personalization, whereas Vietnamese hotels focus strongly on discipline, politeness, professionalism, and service consistency. Novelty/Originality: This study advances hospitality management research by developing a cross-cultural perspective explaining how organizational culture and management control systems shape employee interpersonal service competencies. Unlike previous studies focusing mainly on individual employee characteristics or service training, this study demonstrates how national and organizational contexts influence interpersonal competency development in hospitality organizations